2010
DOI: 10.1002/hec.1700
|View full text |Cite
|
Sign up to set email alerts
|

Regional variations in medical spending and utilization: a longitudinal analysis of US Medicare population

Abstract: One of the perceived symptoms of US Medicare inefficiency is the existence of the dramatic variation in spending and utilization in different areas of the country. This study uses the Continuous Medicare History Sample, a large longitudinal 5% sample of all Medicare beneficiaries from 1974 to 2003, to study the issue. We show that the spending and utilization disparities are significant at the aggregate state level. More importantly, the variation shows signs of narrowing over time, particularly in the earlier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Geographic heterogeneity in healthcare delivery has been investigated in the US Medicare population and is thought to represent a symptom of inefficiency in health care delivery. Some reports estimate that decreased heterogeneity could reduce Medicare expenditures by 15–30% without compromising quality of care delivered 2224 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geographic heterogeneity in healthcare delivery has been investigated in the US Medicare population and is thought to represent a symptom of inefficiency in health care delivery. Some reports estimate that decreased heterogeneity could reduce Medicare expenditures by 15–30% without compromising quality of care delivered 2224 .…”
Section: Discussionmentioning
confidence: 99%
“…Geographic heterogeneity in health care utilization has been rigorously studied in the US Medicare population and is thought to represent a symptom of inefficiency 22, 23 . One study of Medicare expenditures found significant geographic variation that persists after controlling for demographics and health status of populations, and hypothesized that Medicare reform could reduce Medicare spending by 15% 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Although some variation in patterns of care is expected, resulting from differences in disease presentation and patient preference, wide variations can indicate inefficiency in overall health care delivery (18)(19)(20). Quantifying and understanding the drivers of this variability can identify barriers to more equitable health care delivery.…”
Section: Introductionmentioning
confidence: 99%
“…The US literature offers estimates that the 'adoption of conservative, safe practices' could save 15-40 per cent of the vast Medicare budget. 2,5 The track record of English privatisations is unimpressive. As predicted 15 years ago,…”
Section: Privatisation: Providing Health Carementioning
confidence: 99%